A wearable piezoelectro-triboelectric sensor with nanocomposite electrodes for human physiological detection. (1st June 2022) - Zhou, Nannan; Ao, Hongrui; Chen, Xiaoming; Jiang, Hongyuan
Abstract: The detection capability of many electronic sensors is easily interfered by the external turbulent environment. The sensor integrated with different power generation mechanisms can realize multi-states detection by coupling voltage signals. Herein, a flexible wearable bracelet-structure piezoelectro-triboelectric sensor with nanocomposite electrodes (NCEP-TS) is designed and fabricated by nanoparticle doping and thin-film technologies. To investigate its sensing properties, we conducted systematic wearability experiments with consideration of acceleration, temperature, ultraviolet (UV) rays, magnetism, and composite physical fields. The experimental results indicate that the sensitivities of the NCEP-TS reach 1.4 V/g and 0.73 V/mm, and the hystereses are only 2.6% and 2.5%, which is a significant enhancement compared with that of the piezoelectro-triboelectric sensor with single metal electrodes (SMEP-TS). In addition, the stability of the NCEP-TS exceeds that of the SMEP-TS by more than 41.25%. It can be concluded that the NCEP-TS has excellent characteristics, such as high sensitivity, high stability, and low hysteresis. It is worth noting that the flexible feature of the NCEP-TS can provide wearable comfort to realize synchronous detection of pulse and velocity signals. Meanwhile, the output power of the NCEP-TS reaches milliwatt (mW) level in the experiment, which demonstrates the self-powered capability of this sensor. This work provides a reference for improving the sensing properties of the wearable sensor from the electrode perspective. Therefore, the NCEP-TS is a potential alternative for the application of wearable sensors in the field of human physiological monitoring. Graphical Abstract: ga1 Highlights: A nanocomposite electrode is fabricated by nanoparticle doping and thin-film technologies. The NCEP-TS shows excellent sensing properties including high sensitivity, low hysteresis and high stability. The NCEP-TS achieves the synchronous detection of two physiological signals due to the flexible bracelet structure.